MICROCONVECTION WITH A SCALE OF THE ORDER OF TENS OF KILOMETERS, AT THE JUNCTION BETWEEN THE MID-OCEAN RIDGE AND A FRACTURE ZONE - Gavrilov S.V.; Boyko A.N.; Diaman A.M. (My University, 1990)
The matter that ascends toward mid-ocean ridge because of large-scale mantle circulation (on the order of the dimensions of the lithospheric plates) undergoes partial fusion. The result is the accumulation of a layer of a low-viscosity partial molten material under the ridge several dozen kilometers thick. The largest accumulations of partially molten light material of extremely low viscosity occur under the ridge at distances from the junction zone greater than Δy, rather than directly in the vicinity of that zone. A layer of extremely low viscosity (LELV) matter, tens of kilometers thick, may thus be generated at those distances. If the LELV is sufficiently thick, an anomalous heat flux from the mantle to the axis of the ridge may transfer through the layer by convection. We call this convection (through the LELV) a microconvection, to distinguish it from a convection with a typical cell size of hundreds of kilometers. We present a finite element model to simulate this phenomena.